A violência doméstica: a intervenção dos técnicos de acompanhamento na construção de projectos de vida alternativos: um estudo de caso. - Marques, Ana Paula Teixeira (2009)
A violência doméstica tornou-se um fenómeno social de grande complexidade, que não pode ser tratado de forma superficial, seja por parte daqueles que intervêm tecnicamente, seja por parte das vítimas e agressores, pois trata-se da vida real de muitos indivíduos ou sujeitos. Deste modo, tornou-se necessário analisar a violência doméstica, procurando perceber o papel dos agentes, em especial dos técnicos, que acompanham as vítimas de violência doméstica na construção do seu projecto de vida. Para a realização deste estudo, fiz uma abordagem dos diferentes conceitos de família e formas de organização familiar, tanto no modelo tradicional como no moderno, analisando os diferentes conceitos de violência doméstica, fundamental neste trabalho, em virtude da complexidade e controvérsia que a sua definição implica para diferentes autores e abordagens teóricas. Naturalmente que, se o tema da violência doméstica atravessa todo o trabalho, era indispensável ouvir as vítimas desta problemática quanto ao seu sofrimento, coragem e resiliência, ou abandono do lar e acompanhamento recebido. Assim sendo, e porque pretendi fazer uma análise à forma como é realizado o acompanhamento e intervenção por parte dos técnicos, este trabalho apresenta ainda uma investigação empírica realizada através da elaboração de inquéritos por questionário e entrevistas a técnicos (Assistente Social, Educador Social e Psicólogo) e entrevistas a vitimas de violência doméstica. O tratamento e análise dos dados permitiram confirmar, em larga medida, a fundamentação teórica apresentada na primeira parte do estudo onde se verificou haver a divergência no conceito de violência doméstica, as vítimas serem predominantemente do sexo feminino e os agressores do sexo masculino, os vários motivos que levam as vítimas a permanecer na relação e a importância do papel dos técnicos de acompanhamento na definição de projectos de vida alternativos. Domestic violence became a social complex phenomenon today and, therefore, it cannot be looked upon superficially, both by those who are technically involved in it and also by the victims and aggressors themselves, as it refers to the actual life of many individuals. Thus, it became necessary to analyze domestic violence, while trying to understand the role played by the experts/technicians who give support to the victims and help them to (re)design their project of life. To fulfill this research study I approached the several concepts of family and form of family organization, both in the traditional and modern perspective, I analyze the concept of domestic violence, fundamental to this study, due to its complexities and controversy, and theoretical approaches. As expected, the theme of domestic violence is present along the whole work and it became indispensable to hear the voices of the victims regarding their sufferings, courage and resilience, and/or home leave and support received. Following this line of thought, and because I intended to analyze how support and intervention by the experts is given, this work presents empirical data. The data were obtained by means of a questionnaire and an interview to the experts (Social Worker, Social Educator, and Psychologist), and interviews to the victims of domestic violence. The treatment and analysis of data allowed to confirm, in general, the theoretical basis presented in the first part of this study, namely the different concepts of domestic violence, the fact that victims tend to be female and aggressors males, the reasons why victims tend to remain in the home, and the importance of the role played by the experts in helping to design alternative life projects.Domestic violence became a social complex phenomenon today and, therefore, it cannot be looked upon superficially, both by those who are technically involved in it and also by the victims and aggressors themselves, as it refers to the actual life of many individuals. Thus, it became necessary to analyze domestic violence, while trying to understand the role played by the experts/technicians who give support to the victims and help them to (re)design their project of life. To fulfill this research study I approached the several concepts of family and form of family organization, both in the traditional and modern perspective, I analyze the concept of domestic violence, fundamental to this study, due to its complexities and controversy, and theoretical approaches. As expected, the theme of domestic violence is present along the whole work and it became indispensable to hear the voices of the victims regarding their sufferings, courage and resilience, and/or home leave and support received. Following this line of thought, and because I intended to analyze how support and intervention by the experts is given, this work presents empirical data. The data were obtained by means of a questionnaire and an interview to the experts (Social Worker, Social Educator, and Psychologist), and interviews to the victims of domestic violence. The treatment and analysis of data allowed to confirm, in general, the theoretical basis presented in the first part of this study, namely the different concepts of domestic violence, the fact that victims tend to be female and aggressors males, the reasons why victims tend to remain in the home, and the importance of the role played by the experts in helping to design alternative life projects.